The application of tunable tridendate P‐based ligands for the Ru(II)‐catalysed transfer hydrogenation of various ketones. (16th September 2014) - Meriç, Nermin; Durap, Feyyaz; Aydemir, Murat; Baysal, Akın
<x xml:space="preserve">Abstract</x> Two novel versatile tridendate aminophosphine–phosphinite and phosphinite ligands were prepared and their trinuclear neutral ruthenium(II) dichloro complexes were found to be effective catalysts for the transfer hydrogenation of various ketones in excellent conversions up to 99% in the presence of 2‐propanol/NaOH in 0.1 M isopropanol solution. Particularly, [Ru3(PPh2OC2H4)2 N–PPh2(η6‐p‐cymene)3Cl6] acts as an excellent catalyst giving the corresponding alcohols in excellent conversion up to 99% (turnover frequency ≤ 1176 h−1). A comparison of the catalytic properties of the complexes is also discussed briefly. Furthermore, the structures of these ligands and their corresponding complexes have also been clarified using a combination of multinuclear NMR spectroscopy, infrared spectroscopy and elemental analysis. 1H–13C HETCOR or 1H–1H COSY correlation experiments were used to confirm the spectral assignments. Copyright © 2014 John Wiley & Sons, Ltd.